ESTIMATED TIME FOR CUTTING STEEL PROFILES USING A BANDSAW MACHINE IN THE REFINERY DEVELOPMENT MASTER PLAN FABRICATION PROCESS - Abthal Mahdi; Deri Teguh Santoso; Iwan Nugraha Gusniar; Boni Sena (TRAKSI, 2023)
Refinery Development Master Plan (RDMP) is a facility development project to increase the capacity of oil refineries, one of which is by building Pipe Rack. When making Pipe Rack with steel structure, time estimation is needed so that the fabrication process flow can run according to the planned time. One of the fabrication processes is the process of cutting profile steel using a Bandsaw machine. The estimated time of cutting profiled steel using a Bandsaw machine can be determined by the values that affect the cutting process so that initial data such as the value of cutting speed, feeding motion, sawblade type, and the type and dimensions of profiled steel to be cut are required. After knowing the initial data, the calculation of the estimated cutting time can be known with several equations. In the initial data, the feed motion is 5 mm / rotation with a sawblade length of 7600 mm and the dimensions of the profile steel to be cut are 400x200 mm. The machining time is 21.14 minutes with a cutting speed of 15,099.34 mm / minute. After obtaining the cutting speed value on the bandsaw machine, the estimated machining time of several variations of profile steel dimensions and different bandsaw machine feed motions can be determined. From the simulation results of several variation values of cutting speed and feeding motion, the longest cutting time is 21.28 minutes with a cutting speed of 15000 mm/minute and 47 minutes with a feeding motion of 2 mm/rotation. Meanwhile, the fastest cutting time is 10.64 minutes with a cutting speed of 30000 mm/min and 10.43 minutes with a feeding motion of 9 mm/rotation.